Dynamic modeling and analysis of the looped space tether transportation system based on ANCF - Yang, Jie; Wang, Qingtao; Zhang, Zhiyong; Liu, Zhendong; Xu, Shidong; Li, Gangqiang (International journal of mechanical system dynamics, 2022)
A high‐fidelity multibody‐system dynamic model of the looped tether transportation system (L‐TTS) is proposed in this study to study its large deformation as well as large overall motion. The absolute nodal coordinate formulation (ANCF)‐based gradient‐deficient beam element is employed to establish the accurate model of the two flexible tethers subject to large deformations. The relative movement of climbers along tethers is described by using the sliding joint model based on ANCF. To reduce the collision risks between tethers and climbers, two libration suppression strategies, namely, the decelerated motion of climbers relative to tethers and multiple climbers per tether are investigated in this study. Several numerical simulations not only validate the effectiveness of the two strategies in reducing the collision risks between climbers and tethers, the overall librations of L‐TTS, and the magnitudes of the longitudinal elastic force of tethers, but also verify the good performance of the high‐fidelity model proposed in this study for dynamic simulation of the L‐TTS in microgravity conditions.